P77: Clonal evolution of breast tumor during neoadjuvant chemotherapy and metastasis. Issue 1 (November 2015) - Litviakov, N.; Ibragimova, M.; Tsyganov, M.; Kazantseva, P.; Slonimskaya, E.; Cherdyntseva, N.
Abstract : Background: There are numerous evidences suggesting that tumor evolution follows the laws of Darwinian evolution, whereby individual tumor cell clones have private genetic aberrations, including chromosomal abnormalities. The combined effect of genetic instability and differential selective pressures of the microenvironment and chemotherapy can result in the creation of new tumor clones (Navin et al., 2011; Ng et al., 2012). The aim of this study is to show breast tumor clonal evolution during neoadjuvant chemotherapy (NAC) using microarray analysis. Material and methods: Breast cancer patients ( n  = 26) with stage IIA to IIIC (T1-4N0-3M0), were treated with NAC (FAC or CAX regimens). DNA was extracted from 26 samples of tumor tissue derived before or after NAC using QIAamp DNA mini Kit (Qiagen, Germany). Copy Number Aberrations (CNA, deletions and amplifications, or Loss and Gain, respectively) and number of mutant clones were detected in pre- and post-NAC tumor samples using the high density microarray platform Affymetrix (USA) CytoScanTM HD Array. This study was approved by Tomsk Cancer Research Institute review board. Results: We have revealed that 19% (5/26) of patients during the NAC showed the decrease in the number of mutant clones and CNA frequency right up to their complete elimination (genetic regression) at one case. In 7 (27%) cases chemotherapy had no any effect on number of mutant clones and the frequency of CNA in tumor. In the tumors of 10 patients the elimination of some mutant clones as well as the formation of new clones with deleted genetic material occurred under the influence of chemotherapy. 6 patients have demonstrated the appearance of new tumor clones with gene amplifications which were associated with the development of metastases in 83% of cases (5/6). All other patients ( n  = 21) who has not acquired the new tumor clones with Gain function mutation after NAC did not manifest distant metastasis in 5-year follow-up (Kaplan–Meier, p  = 0.00001 Log-rank test). Conclusion: The first time evidence is presented that the formation of new tumor clones may occur during the NAC. Metastasis of breast cancer is associated with the appearance of new clones with DNA amplifications. Detection of these clones allow getting new prognostic factor in breast cancer. The study was supported by theRussian Foundation for Basic Research – Russia (Project 15-04-03091).